PWE-035 The Introduction of a Weekly General Anaesthetic Ercp List Improves Desired Duct Cannulation and Duct Drainage Rates. (4th June 2013) - Neale, J; Ellis, R; Goggin, P; Fowell, A
Abstract : Introduction: ERCP remains a key, but potentially complex endoscopic modality. ERCP procedures can be prolonged and consequently require higher dose and longer duration of conscious sedation. The use of anaesthetist-led deep sedation or general anaesthesia (GA) has been clearly demonstrated as a safe alternative to the use of conscious sedation 1, 2 . However, the effect of general anaesthesia on the success of ERCP has not been well studied. The aim of this study was to examine the impact of the introduction of a weekly anaesthetist-led GA ERCP list on the successful completion of ERCP. Methods: The data for all ERCP procedures performed within our unit was retrieved from the local endoscopic database covering the period one year before (BGA) and one year after (AGA) introduction of a weekly GA ERCP list in January 2012. Data regarding selective cannulation rates, patient and endoscopist demographics and complications were analysed. Success at ERCP was defined as selective deep cannulation of the targeted duct and the successful drainage of obstructed systems when required. Results: A total of 713 ERCP cases were examined. ERCPs were performed by 3 experienced endoscopists within a single endoscopy unit. 357 cases were performed prior to regular GA list introduction and 356 cases after. There were 28 cases performed under GA in the BGA group and 81 in the AGA group (p < 0.01). There was no statistical difference in patient age or gender ratio. Following the introduction of regular GA ERCP lists, the overall procedural success rate increased from 94.7% to 98.3% (p < 0.01). Procedural failure did not occur in any of the 109 cases performed under GA. Reasons for failure at ERCP were multiple, with sedation failure directly quoted in 3 of the 25 cases. Use of sedation reversal agents was lower in the AGA group (8 vs 1 cases, p < 0.05). Conclusion: The introduction of a weekly general anaesthetic ERCP list has improved desired duct cannulation and drainage success within our endoscopy unit. This advantage of anaesthetist-led sedation has not been previously demonstrated. The mechanism of improved success is likely to be multi-factorial in origin. Although agitation and sedation failure were cited in only a minority of procedural failures, we believe the increased control and safety afforded allows the endoscopist to successfully perform more challenging interventions. These data may support the wider introduction of anaesthetist-led sedation/general anaesthesia for ERCP. Disclosure of Interest: None Declared. References: Bo LL et al. Propofol vs traditional sedative agents for endoscopic retrograde cholangiopancreatography: a meta-analysis. World J Gastroentero l. 2011 Aug 14; 17(30):3538–43. Garewal D et al. Sedative techniques for endoscopic retrograde cholangiopancreatography. Cochrane Database Syst Rev . 2012 Jun 13; 6:CD007274.